2018
DOI: 10.1039/c8fo01146j
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification and the anti-hypertensive effect of a novel angiotensin I-converting enzyme (ACE) inhibitory peptide from Ruditapes philippinarum fermented with Bacillus natto

Abstract: Hypertension is known as an important factor in cardiovascular disease. An angiotensin-I-converting enzyme (ACE) inhibitor is one of the synthetic drugs that is widely used to control hypertension. Here, we have prepared and investigated the ACE inhibitory peptide from Ruditapes philippinarum fermented with Bacillus natto. The fermented product obtained under optimized fermentation conditions exhibited ACE inhibitory activity. The ACE inhibitory peptides were purified by ultrafiltration, gel filtration chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…Najafian & Babji (2018) mentioned that the high antioxidant activity of the peptides is attributed to the presence of high levels of hydrophobic amino acid residues and their interactions in the peptides. By using Bacillus natto to ferment Ruditapes philippinarum clams under the optimal conditions (5% inoculum, 1:25 solid-to-water ratio, and 10% additional sugar at 45 • C for 24 hr), Chen, Gao, et al (2018) The study showed that P1 demonstrated a higher antioxidant activity compared to P2. The presence of hydrophobic amino acids (Ile, Ala, and Pro) and basic amino acids (Lys) in the peptide sequences is believed to contribute to the high antioxidant activity of the fermented Loma fish.…”
Section: Fish and Shellfishmentioning
confidence: 99%
See 3 more Smart Citations
“…Najafian & Babji (2018) mentioned that the high antioxidant activity of the peptides is attributed to the presence of high levels of hydrophobic amino acid residues and their interactions in the peptides. By using Bacillus natto to ferment Ruditapes philippinarum clams under the optimal conditions (5% inoculum, 1:25 solid-to-water ratio, and 10% additional sugar at 45 • C for 24 hr), Chen, Gao, et al (2018) The study showed that P1 demonstrated a higher antioxidant activity compared to P2. The presence of hydrophobic amino acids (Ile, Ala, and Pro) and basic amino acids (Lys) in the peptide sequences is believed to contribute to the high antioxidant activity of the fermented Loma fish.…”
Section: Fish and Shellfishmentioning
confidence: 99%
“…By using Bacillus natto to ferment Ruditapes philippinarum clams under the optimal conditions (5% inoculum, 1:25 solid‐to‐water ratio, and 10% additional sugar at 45 °C for 24 hr), Chen, Gao, et al. (2018) managed to obtain a peptide (VISDEDGVTH) with high ACE‐I activity (IC 50 = 8.16 µM) after sequential fractionation. Due to its small molecular weight, the peptide was stable against simulated gastrointestinal digestion.…”
Section: Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of adults suffering from hypertension is estimated to increase to 1.6 billion worldwide by 2025 [2]. Angiotensin I converting enzyme (ACE) is regarded a crucial enzyme in regulating blood pressure by promoting the conversion of angiotensin I to angiotensin II in the circulatory or endocrine of human renin-angiotensin system [3,4]. In addition, ACE also converts the vasodilator bradykinin into an inactive peptide via kallikrein–kinin systems [5].…”
Section: Introductionmentioning
confidence: 99%